Controlled immobilization strategies to probe short hyaluronan-protein interactions - Minsky, Burcu Baykal; Antoni, Christiane; Böhm, Heike (Scientific reports, 2016)
Well-controlled grafting of small hyaluronan oligosaccharides (sHA) enables novel approaches to investigate biological processes such as angiogenesis, immune reactions and cancer metastasis. We develop two strategies for covalent attachment of sHA, a fast high-density adsorption and a two-layer system that allows tuning the density and mode of immobilization. We monitored the sHA adlayer formation and subsequent macromolecular interactions by label-free quartz crystal microbalance with dissipation (QCM-D). The modified surfaces are inert to unspecific protein adsorption and yet retain the specific binding capacity of sHA. Thus they are an ideal tool to study the interactions of hyaluronan-binding proteins and short hyaluronan molecules as demonstrated by the specific recognition of LYVE-1 and aggrecan. Both hyaladherins recognize sHA and the binding is independent to the presence of the reducing end.
Gesehen am 23.06.2020